The development of a driver assist system with distance estimation using a single camera / Erma Rahayu Mohd Faizal Abdullah - Mohd Faizal Abdullah, Erma Rahayu (Institute of Graduate Studies, UiTM, 2013)
In this thesis, an investigation on lane and vehicle tracking on a highway is carried out. The highway is chosen as the test ground due to the one-way flow of traffic, relative straightness of the road and consists of mostly automobiles. This study describes the development of a mid-line generation technique on the road as guidance for drivers to stay in the centre of the road lane they are currently driving on. The technique detects and tracks road lane in a video sequence and draws a virtual mid-line on the screen to guide the driver to stay centred within the lane…